Health service for diabetic foot ulcer patients during covid-19 pandemic - Hermawati Hermawati; Yulius Tiranda; Sukron Sukron (Universitas Muhammadiyah Semarang, 2021)
In early 2020, the whole world was shocked by the COVID-19 pandemic, which impacted all aspects of life. One was changes in the service system and health care for patients with diabetic foot ulcers (DFU). Wound care in DFU patients should be routine but while minimizing hospital visits to reduce the risk of exposure to COVID-19. The objective of this study was to explore the health services provided to DFU patients during the COVID-19 pandemic at the hospital. This study used a literature review approach with six electronic databases, namely National Library, PubMed, Science Direct, ProQuest, Springer Nature, and Wiley, in 2019-2021. The keyword used were health service, diabetic foot ulcer and COVID-19. around 669 articles identified, 12 articles met the inclusion. The articles reviewed were obtained from the result of discussion and validations between researcher and supervisors following the Prisma Guideline. Health services for DFU patients during the COVID-19 pandemic may be conducted through several stages including a) online consultation or telemedicine as the first stage, b) continued with triage process, and c) screening for individual patients needs. Health services for DFU patients during the COVID-19 pandemic have changed according to the following conditions. The first procedure was to conduct an online consultation (telemedicine) to assess the client’s condition related to complaints, then proceed with the triage process to prioritize care and service needs. The health of each patient and screening to check for symptoms of COVID-19 as well as carried out additional screening, CT Thorax and Swab if the patient had to go to the hospital.